Origins of violence in soccer: a psychological survey in southern Brazil - Alex Christiano B. Fensterseiffer; Nivia Marcia Velho; Ruy Jornada Krebs; Mário Luiz C. Barroso; Tatiana Marcela Rotta (Universidade Federal de Santa Catarina, 2007)
This study aimed to analyze the opinions of sports psychologists on the main causes of aggressive attitudes during professional soccer games. Sixteen psychologists from fi rst division teams in Brazil's Southern region were investigated during the fi rst semester of 2004. They indicated the fi ve most important items in a multiple choice list proposed by the researchers, numbering them in order of importance. The data were analyzed both qualitatively and quantitatively, and, in the opinions of this study's participants, the most worrying factors were the importance of a game (41 points), provocation by opponents (37), coaches' attitudes (33), team performance (25) and losing scorelines (23). Results suggest the need for professional teams to take measures internally, with the participation of sports psychologists, and also for external measures to be taken, such as changing certain rules of the game in order to decrease aggressiveness on the soccer field. RESUMO Este trabalho se propôs a analisar, junto a psicólogos do esporte, quais são os principais fatores que originam atitudes agressivas em uma partida de Futebol profi ssional. Foram investigados 16 psicólogos que trabalhavam em equipes das primeiras divisões estaduais da região sul do Brasil, no primeiro semestre de 2004, sendo que estes responderam a uma questão fechada, numerando 5 fatores por ordem de importância. Os dados foram analisados de forma quantitativa e qualitativa, e apresentaram os seguintes fatores como os mais preocupantes para os psicólogos do esporte: importância do jogo (41 pontos), provocações de adversários (37), comportamento do técnico (33), rendimento da equipe (25) e placar adverso (23). Os resultados sugerem a necessidade de atitudes internas aos clubes, com atuação dos psicólogos do esporte, e externas, no que se refere à mudança de regras da modalidade no sentido de minimizar a agressividade em campo.